Evaluasi Kesesuaian Lahan Beberapa Tanaman Pangan pada Lahan Sawah Berbasis Sistem Informasi Geografis di Kecamatan Baturiti - SARI, DJIAN NILAM; TRIGUNASIH, NI MADE; MEGA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Land Suitability Evaluation of Several Food Crops on Rice Fields Based on Geographic Information System in Baturiti Sub-District The need for land will continue to increase along with the growth of the population which increases every year. The results of the land evaluation will provide information and/or directions for land use as needed. This study aims to determine the level of land suitability for the development of food crops, the limiting factors that become obstacles and efforts to improve it, and determine the direction of land use according to its potential. The research was conducted in Baturiti Sub-District. This research used survey methods and soil sample analysis in the laboratory. The land suitability classification method is carried out by matching. The results showed that the actual land suitability for food crops in Baturiti Sub-District was classified as S1 (very suitable) to S3 (marginally suitable), with the limiting factors of temperature, rainfall, and nutrient avaibility (N-Total and P 2 O 5 ). Improvements that can be made to the limiting factors include making drainage channels, fertilizing with organic fertilizers and containing N and P elements, so that the potential land suitability classified as S1 (very suitable) to S2 (moderate suitable) with a temperature limiting factor. Land use directions for food crops commodities in Baturiti Sub-District are paddy, corn, and soybean.